Pengembangan Modul Ajar IPAS Berbasis Pembelajaran Berdiferensiasi Terintegrasi Kompetensi Sosial Emosional - Marisa, Lilin; Raharjo, Tri Joko; Wardani, Sri (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Based on the results of pre-research through interviews, observation, and documentation of student learning outcomes in class IV of Elementary Schools in Gemawang District, Temanggung Regency, it was found that the problem of learning independence and scientific literacy of students was still low. This is influenced by the lack of teaching modules that integrate differentiated learning integrated with social emotional abilities. The purpose of this research is to describe the characteristics, examine the feasibility and test the effectiveness of the science teaching modules based on differentiated learning integrated social emotional competence. The type of research used is Research and Development (R&D) with the ADDIE model. In this study there are 5 stages, namely: (1) analysis; (2) design; (3) development; (4) implementation; (5) evaluation. Data collection techniques using tests, questionnaires, observations, interviews, and documentation. The data were processed using comparative data analysis (t-test) with the help of SPSS 25. The results showed that the development of science-based science teaching modules based on differentiated learning integrated with social-emotional content could increase the independent learning and scientific literacy of students in the experimental class with the results obtained in the N-Gain product trial of 0.79 with a high ratio. Keywords: Differentiated Learning, Social Emotional Competence, Independent Learning and Scientific Literacy